Training standards statements of family medicine postgraduate training: a review of existing documents worldwide - Flum, Elisabeth; Berger, Sarah; Szecsenyi, Joachim; Marquard, Sabine Nina (PLOS ONE, 2016)
Introduction For the effective and safe management of complex care needs for patients in community settings, high quality family medicine (FM) training programmes are needed. In less primary care oriented countries, training standards statements for FM postgraduate training are less commonly found. The aim of this study was to review international training standards statements in FM postgraduate training and to catalogue these statements to be used as a best practice standard guide for FM training programs in Germany. Materials and Methods A structured three-tiered search was performed: a systematic literature search in MEDLINE®; a search of international indicator databases; and a search in grey literature, consisting of a survey of international experts and a search in “Google (Scholar)”. From all identified documents, training standards statements were extracted, translated and summarized into categories referring to the same quality aspect. Results The search strategy revealed 25 relevant documents (MEDLINE® n = 15, databases n = 2, experts n = 7, “Google” n = 1), containing 337 training standards statements. These were summarized into 80 statements. They covered structure quality (n = 35); process quality (n = 43); and two training standards statements referred to outcome quality (n = 2). Conclusion A broad range of internationally sourced training standards statements for FM postgraduate training could be identified from countries with well-established primary care systems. Only few statements internationally referred to outcome quality, expressing the difficulty in assessing outcome. The resulting inventory of training standards statements for FM postgraduate training can serve as a resource for institutions seeking to formalise and systematise FM training at regional or national levels.